Ru doped anatase titanium dioxide and its photocatalytic activity of rhodamine B / Muhamad Adam Ramli - Ramli, Muhamad Adam (Faculty of Applied Sciences, 2017)
Pure and ruthenium-doped titanium dioxide (TiO2) nanopartic1es powder were prepared in this study via liquid deposition method. The Ti02 in this study was synthesised from the potassium titanyl phosphate powder and boric acid as fluoride scavenger. The ruthenium element was introduced to the pure Ti02 at different concentrations. The doped concentrations of Ru were varying at 0.1 M, 0.5 M, 0.025 M, 0.00125 M and 0.00625 M respectively. The samples were characterized using X-ray diffraction (XRD), Field Emission Scanning Electron (FESEM) and UV-Vis spectrophotometer. XRD analysis shows that the Ti02 nanopartic1es prepared has anatase structure with a dominant high energy (101) basal plane. The EDX analysis confirms the presence of Ru element in the Ti02 nanopartic1e. FESEM showed the morphological analysis of the sample. The band gaps of the samples lie in the theoretical value obtained from the absorbance using UV-Vis spectrophotometer. Photocatalytic properties of the samples were examined using degradation of Rhodamine B. It was found that pure Ti02 shows poor photocatalytic performance and Ru-doped Ti02 shows an enhancement towards photocatalytic performance. 0.025 M Ru was the optimum concentration while the concentration above this dopant yields poor result of photocatalytic degradation